Can Yogic Breathing Techniques Like Simha Kriya and Isha Kriya Regulate COVID-19-Related Stress? - Rain, Manjari; Subramaniam, Balachundhar; Avti, Pramod; Mahajan, Pranay; Anand, Akshay (Frontiers in Psychology, 2021)
The global impact of Coronavirus Disease 2019 (COVID-19) is tremendous on human life, not only affecting the physical and mental health of population but also impacting the economic system of countries and individual itself. The present situation demands prompt response towards COVID-19 by equipping the humans with strategies to overcome the infection and stress associated with it. These strategies must not only be limited to preventive and therapeutic measures, but also aim at improving immunity and mental health. This can be achieved by yogic breathing techniques. In this perspective, we emphasize the importance of yogic breathing, Simha Kriya and Isha kriya, the simple yet effective breathing techniques.